2017
DOI: 10.1042/bsr20170199
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish models for functional and toxicological screening of nanoscale drug delivery systems: promoting preclinical applications

Abstract: Preclinical screening with animal models is an important initial step in clinical translation of new drug delivery systems. However, establishing efficacy, biodistribution, and biotoxicity of complex, multicomponent systems in small animal models can be expensive and time-consuming. Zebrafish models represent an alternative for preclinical studies for nanoscale drug delivery systems. These models allow easy optical imaging, large sample size, and organ-specific studies, and hence an increasing number of precli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 112 publications
(125 reference statements)
0
28
0
4
Order By: Relevance
“…It has been reported that zebrafish is an excellent model for that purpose since it mimics the complexity of interactions in the human body due to its high degree of homology to human genome and biological systems. Its embryos can be used to monitor phenotypic and genotypic abnormalities upon exposure to toxic agents (Lee et al, 2017). Toxicresponse similarities between zebrafish and mammals have been renowned for small molecules that cause endocrine disruption, reproductive toxicity, behavioral defects, teratogenesis, carcinogenesis, cardiotoxicity, ototoxicity, liver toxicity and others (Zon and Peterson, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that zebrafish is an excellent model for that purpose since it mimics the complexity of interactions in the human body due to its high degree of homology to human genome and biological systems. Its embryos can be used to monitor phenotypic and genotypic abnormalities upon exposure to toxic agents (Lee et al, 2017). Toxicresponse similarities between zebrafish and mammals have been renowned for small molecules that cause endocrine disruption, reproductive toxicity, behavioral defects, teratogenesis, carcinogenesis, cardiotoxicity, ototoxicity, liver toxicity and others (Zon and Peterson, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Biosynthesized nanoparticles have been described for their ability to inhibit/destroy microbial cells. Nanoparticles may be good source for delivery of herbal medicines in the field of health promotion [35].…”
Section: Evaluation Of Antimicrobial Activitiesmentioning
confidence: 99%
“…Zebrafish (Danio rerio) develop most of the main organ systems present in mammals during the first week of life; some organs and tissues have been shown to be similar to those of mammals at anatomic, physiological, and molecular levels [17]. As zebrafish larvae develop in a short period of time, ex utero, and are transparent, they are ideal for nano-particle and drug analysis with noninvasive techniques [18].…”
Section: Introductionmentioning
confidence: 99%